BILATERAL PERSISTENT SCIATIC ARTERY: A CASE REPORT OF A RARE VARIANT WITH CLINICAL IMPLICATIONS
Although rare, the persistence of a sciatic artery is a clinically significant vascular variant, since it is often associated with complications such as aneurysm formation, thrombosis and ischaemia. We present the case of a patient with signs of subacute ischaemia on the right lower limb and a pulsatile mass in the right inferior gluteal region. CT angiography revealed a bilateral persistent sciatic artery (PSA) complicated by aneurysm formation and embolization of distal popliteal artery. Treatment included a femoro-popliteal bypass, ligation of the popliteal artery above the anastomosis and embolization of the aneurysmal lesion.